Two-Stage Optimal Design Method for Asymmetric Base-Isolated Structures Subject to Pulse-Type Earthquakes - Zhang, Jiayu; Qi, Ai; Yang, Mianyue (Buildings (Basel), 2024)
Asymmetric base-isolated structures subjected to severe torsion may suffer further aggravation of their torsional and translational responses under pulse-type earthquakes. To counteract these detrimental impacts, this study introduces a two-stage optimal design method. The first stage involved the application of the NSGA-II algorithm for determining an optimal isolator arrangement—namely, position and category—with the objective of reducing both the maximum interstory rotation of the superstructure and the isolation layer. In the second stage, the inclusion of viscous dampers served to minimize the excessive translational response triggered by pulse-type earthquakes. The influence of these dampers’ positions on the structural response was carefully evaluated. The final application of this optimal design method was demonstrated on an asymmetric base-isolated structure. The results indicated a significant reduction in the translational and torsional responses of the asymmetric base-isolated structure when the two-stage optimal design method was utilized, compared to those of structures designed using traditional conceptual methods. It was found that by installing viscous dampers in the isolation layer along both the x and the y directions—specifically, underneath the mass center of the superstructure (CMS)—the effectiveness of the torsional resistance from the first stage could be effectively maintained.